Vitamin D deficiency and risk of acute kidney injury after ischemic stroke: a propensity-matched cohort study - Hung, Kuo-Chuan; Chang, Li-Chen; Lai, Yi-Chen; Yew, Ming; Liu, Ping-Hsin; Chen, I-Wen (Frontiers in Nutrition, 2026)
BackgroundVitamin D deficiency (VDD) has been linked to adverse outcomes in various clinical settings, but its relationship with post-stroke acute kidney injury (AKI) remains unexplored.MethodsThis retrospective cohort study utilized the TriNetX research network database to identify adult patients with first-documented ischemic stroke between January 2010 and December 2024. Patients were stratified based on serum 25-hydroxyvitamin D levels measured within 6 weeks pre-stroke: VDD group (<20 ng/mL) and control group (≥30 ng/mL). After 1:1 propensity score matching, we compared 30-day and 1–12 month outcomes between groups, with the primary outcome being AKI incidence within 30 days post-stroke.ResultsAfter matching (n = 4,343 per group), patients with pre-stroke VDD demonstrated significantly higher 30-day AKI incidence compared with those with sufficient vitamin D levels (5.3% vs. 3.5%; odds ratio [OR] = 1.55, 95% confidence interval [CI] 1.26–1.92; p < 0.001). VDD was also associated with increased risks of all-cause mortality (OR = 1.63, 95% CI 1.26–2.12), intensive care unit (ICU) admission (OR = 1.55, 95% CI 1.30–1.84), pneumonia (OR = 1.48, 95% CI 1.09–2.02), and dialysis requirement (OR = 2.33, 95% CI 1.36–4.00). Vitamin D insufficiency (20–29 ng/mL) was associated with a milder but significant AKI risk increase (OR = 1.39, 95% CI 1.12–1.72; p = 0.003). The adverse effect of VDD persisted during 1–12 month follow-up, with higher risks of AKI (hazard ratio [HR] = 1.32, 95% CI 1.13–1.55) and progression to end-stage renal disease (HR = 1.69, 95% CI 1.16–2.46).ConclusionPre-stroke VDD is associated with increased risk of post-stroke AKI and other adverse outcomes. The observed dose-dependent relationship suggests potential benefits from optimizing vitamin D status. These findings highlight the importance of assessing vitamin D levels in stroke risk stratification and suggest potential preventive strategies.